2013
DOI: 10.1177/2048872613483592
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced cardiomyopathy (Tako-Tsubo syndrome) in Austria

Abstract: Background: Tako-Tsubo syndrome (TS) is a still rarely diagnosed clinical syndrome, which is characterized by acute onset of chest pain, transient cardiac dysfunction with (frequently) reversible wall motion abnormalities (WMAs), but with no relevant obstructive coronary artery disease. Methods and results: Among 179 consecutive patients with proven diagnosis of TS that were retrospectively analysed in this multicentre registry, women represented the majority of patients (94%) while only 11 men (6%) developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
2
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 24 publications
1
23
2
9
Order By: Relevance
“…38 As a matter of fact, patients with Takotsubo Syndrome have a prevalence of comorbid cardiovascular risk factors higher than the general population and similar to that seen in patients with acute myocardial infarction. 39 In a large series of 305 women with acute left ventricular dysfunction, Parodi et al found no difference in the prevalence of hypertension, hypercholesterolemia, and smoking between those with Takotsubo Syndrome and those with anterior myocardial infarction. 40 The possibility exists therefore that the susceptibility to Takotsubo Syndrome may, in part, be related to a high prevalence of risk factors leading to premorbid endothelial dysfunction, 41 The pratical implication of the findings of the COUNTS study is of relevance.…”
Section: Resultsmentioning
confidence: 97%
“…38 As a matter of fact, patients with Takotsubo Syndrome have a prevalence of comorbid cardiovascular risk factors higher than the general population and similar to that seen in patients with acute myocardial infarction. 39 In a large series of 305 women with acute left ventricular dysfunction, Parodi et al found no difference in the prevalence of hypertension, hypercholesterolemia, and smoking between those with Takotsubo Syndrome and those with anterior myocardial infarction. 40 The possibility exists therefore that the susceptibility to Takotsubo Syndrome may, in part, be related to a high prevalence of risk factors leading to premorbid endothelial dysfunction, 41 The pratical implication of the findings of the COUNTS study is of relevance.…”
Section: Resultsmentioning
confidence: 97%
“…Prognosis of patients with TTC is generally thought to be favourable with complete recovery of LV function within several weeks . However, the initial presentation can be accompanied by fatal complications, including cardiogenic shock, congestive heart failure, and lethal arrhythmias, leading to an in‐hospital disease‐related mortality of 2–8.7% …”
Section: Introductionmentioning
confidence: 99%
“…Recently, a registry‐based study suggested a similar long‐term prognosis in TTC patients compared with patients with myocardial infarction . Overall, long‐term mortality rates after >2 years of follow‐up are heterogeneous ranging from 5% to 17%, and it is unclear whether or not clinical characteristics, stress types, and/or ballooning patterns affect long‐term prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Istnieje udokumentowany przypadek pacjentki, u której choroba wystąpiła 4-krotnie [7]. W więk-szości przypadków rokowanie jest korzystne, u niektórych chorych jednak dochodzi do groźnych powikłań, które mogą być nawet przyczyną zgonu [8][9][10][11][12][13][14].…”
Section: Wstępunclassified